Peran Kepuasan Kerja Terhadap Kinerja Pada Guru Pegawai Negeri Sipil (PNS) di Yogyakarta - Tentama, Fatwa (Jurnal Psikologi, 2015)
The problems faced by organizations is employee performance tends to decline over time resulting ineffectiveness of the organization. One of the factors that affect performance is job satisfaction. This study aims to determine empirically the correlation between job satisfaction and performance of the civil servant teachers. Subjects were 29 civil service teachers both male and female who become permanent employees and has worked at least 1 year in SLB Negeri 1 Bantul Yogyakarta. Data were collected using the Job Satisfaction Scale and theÂ Performance Scale. Pearsonâ€™s product moment correlation were used to test the relationship between job satisfaction and teacher performance. The results showed that there is a significant positive correlation between job satisfaction and performance of the civil servant teachers (rxy= .551; p= .001). The more satisfied the teachers, the higher their performance.